The Ranking Function for Solving the Fuzzy Hotelling T2 Test - Thamer, Esraa Dhafer; Hussein , Iden Hasan (Iraqi Journal of Science, 2021)
A multivariate control chart is measured by many variables that are correlated in production, using the quality characteristics in any product. In this paper, statistical procedures were employed to find the multivariate quality control chart by utilizing fuzzy Hotelling test. The procedure utilizes the triangular membership function to treat the real data, which were collected from Baghdad Soft Drinks Company in Iraq. The quality of production was evaluated by using a new method of the ranking function.